PELAKSANAAN PEMBONGKARAN BANGUNAN YANG TIDAK MEMILIKI IMB DI KECAMATAN TAMPAN - Muhammad Rio Andalas Tanjung; Ardiansyah; Silm Oktapani (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
The purpose of this research is to explain the form of implementation, obstacles faced, and efforts to overcome obstacles in demolishing buildings that do not have building permits in Tampan District based on Regional Regulation Number 1 of 2010 concerning Building Permit Levy. The research method used is a sociological research method on legal effectiveness. Through observation techniques, structured interviews, questionnaires and literature review. Data analysis used qualitative analysis, and used deductive methods. There were 5 demolitions of buildings did not have building permits in Tampan District in 2019 and 7 in 2020 in Tampan District. Based on data from warning letters attached in 2019, there were 172 illegal buildings and 139 illegal buildings in 2020 that had not yet been followed up in Tampan District. The obstacle faced is the limited number of members of the relevant department so that they cannot carry out control effectively in Tampan District. There is no agenda for controlling illegal buildings that do not have a permit in Tampan District. Efforts that need to be made are scheduling the control of illegal buildings that do not have a permit in Tampan District, and even strict sanctions need to be implemented against people who commit violations. It is necessary to increase the number of relevant service personnel on duty in the Tampan District area, and provide legal outreach/counseling for the entire community.